(untitled) (Experimental biology, 2020)
The article presents the results of studies of early spring plant communities, conducted in May 2018 in the Zhongar-Alatau National Park. Habitats of plants from the Red Data Book of Kazakhstan were identified: Aquilegia vitalii, Fritillaria pallidiflora, Adonis tianschanica, Malus sieversii, Malus niedzwetzkyana, Paeonia anomala, Crocus alatavicus, Tulipa brachystemon, Tulipa patens. Among them, there are narrow endemics Aquilegia vitalii, Tulipa brachystemon. Plant communities with rare species belong to meadow, shrub, and forest types of vegetation, distributed on meadows of mountain slopes and gorges in combination with small-leaved and coniferous forests, and petrophytic shrubs on stony slopes. For each rare species the altitudinal belt, plant community and phytocenotic role were determined. A rare species, which has a limited distribution on the northern macroslope of the Zhetysu Alatau has been identified as a bell-shaped pasqueflower (Pulsatilla campanella). The species does not have wide area of distribution; it forms sparse populations in the belt of dark coniferous forests and meadows. Vulnerable due to the fact that it is actively used in traditional medicine. It is recommended to include it into the regional Red Data Book. Key words: Zhetysu Alatau, early-flowering species, rare plants, altitudinal zonality, plant communities.